2018
DOI: 10.1016/j.cell.2017.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of GPCR Drug Targets

Abstract: SummaryNatural genetic variation in the human genome is a cause of individual differences in responses to medications and is an underappreciated burden on public health. Although 108 G-protein-coupled receptors (GPCRs) are the targets of 475 (∼34%) Food and Drug Administration (FDA)-approved drugs and account for a global sales volume of over 180 billion US dollars annually, the prevalence of genetic variation among GPCRs targeted by drugs is unknown. By analyzing data from 68,496 individuals, we find that GPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
460
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 506 publications
(465 citation statements)
references
References 67 publications
(92 reference statements)
1
460
0
4
Order By: Relevance
“…4B). To account for the fact that almost 25% of the GPCR functional sites show an average of at least one polymorphism, we mapped all GPCR variants 25 and site-directed mutations 26 from the GPCRdb 4 to each GPCR structure. Flexible options allow users to change the color of the map type (classical fo-fc or composite 2fo-fc), style (e.g.…”
Section: Gpcrmd Viewer : Sharing and Interactive Visualization Of Gpcmentioning
confidence: 99%
“…4B). To account for the fact that almost 25% of the GPCR functional sites show an average of at least one polymorphism, we mapped all GPCR variants 25 and site-directed mutations 26 from the GPCRdb 4 to each GPCR structure. Flexible options allow users to change the color of the map type (classical fo-fc or composite 2fo-fc), style (e.g.…”
Section: Gpcrmd Viewer : Sharing and Interactive Visualization Of Gpcmentioning
confidence: 99%
“…117 Furthermore, recent studies indicate considerable genetic variation in drug-targeting sites of many G-protein coupled receptors (GPCRs), which may provide an area of furtive research for the endocrine field. 118 Likewise, another recent study demonstrated asthma patients carrying specific genetic variants in the PDGFR gene were at increased risk of steroid-induced adrenal suppression. 119 Thus, it is possible that genetic testing may not only be used to guide therapy but also to predict those at increased risk of adverse endocrine outcomes.…”
Section: Incidental Findingsmentioning
confidence: 99%
“…Other emerging areas for genetic testing include pharmacogenomic assays to identify individuals with enhanced, reduced or adverse responses to specific therapies (eg association of aminoglycoside ototoxicity with a mitochondrial DNA mutation) . Furthermore, recent studies indicate considerable genetic variation in drug‐targeting sites of many G‐protein coupled receptors (GPCRs), which may provide an area of furtive research for the endocrine field . Likewise, another recent study demonstrated asthma patients carrying specific genetic variants in the PDGFR gene were at increased risk of steroid‐induced adrenal suppression .…”
Section: Future Directions and Concluding Remarksmentioning
confidence: 99%
“…When dose adjustment occurs, it is usually based on a single covariate such as body weight (eg, low‐molecular‐weight heparins) or renal function (eg, oseltamivir) . However, our understanding of PK/PD now goes beyond these simple covariates in the PI to include the “unseen” physiological and molecular determinants of drug disposition and response—DMET activities, organ sizes and blood flows, inflammatory status, gut microbiome, genetics of molecular targets, and so forth . The word unseen is used here because such covariates are either not currently tested for in clinical practice, or if they are tested for, most doctors are unclear about how to action the result, such as pharmacogenomic test results for DMETs, that is, the prescriber is literally blind to their importance.…”
Section: Informing Pbpk Companion Mipd Tools With Individual Patientmentioning
confidence: 99%